Accuracy of ultrasound beyond 14 weeks to determine chorionicity of twin pregnancies - Momberg, Zoe (Department of Obstetrics and Gynaecology, 2016)
Determining the chorionicity of twin pregnancies is extremely important as this influences the frequency of surveillance, timing of delivery and management of complications. Monochorionic twins have 2.5 times the perinatal mortality of dichorionic twins, and in the case of a single intra-uterine fetal demise, the surviving twin of a monochorionic pair is at significant risk of neurological damage compared to a dichorionic pregnancy. Chorionicity can be accurately determined before 14 weeks gestation using the lambda or T-sign. After 14 weeks, these ultrasonographic signs become less reliable and the pregnancy may be assumed to be monochorionic for management purposes. The implication of this assumption is that on occasion premature dichorionic fetuses may be delivered unnecessarily. In South Africa, many women have their first antenatal visit after the first trimester or are not scanned by an experienced sonographer until after 14 weeks. There is thus a need for an accurate means to determine chorionicity in the second and third trimesters.